Higher mitochondrial oxidative capacity is the primary molecular differentiator in muscle of rats with high and low intrinsic cardiorespiratory fitness - Johanna Y. Fleischman; Françoise Van den Bergh; Nicole L. Collins; Madelyn Bowers; Daniel A. Beard; Charles F. Burant (Elsevier, 2023)
Objective: Cardiorespiratory fitness (CRF) is tightly linked with health and longevity and is implicated in metabolic flexibility and substrate metabolism. The high capacity runner (HCR) and low capacity runner (LCR) rat lines are a genetically heterogeneous rat model selected and bred for CRF that reflect CRF in humans by exhibiting differences in nutrient handling. This study aims to differentiate the intrinsic substrate preference of the HCR compared to LCR rats to better understand the intersection of mitochondrial respiration and intrinsic CRF. Methods: We performed bulk skeletal muscle RNA-Sequencing on male and female HCR and LCR rats and assessed the effect of rat line on mitochondrial gene expression pathways using the MitoCarta3.0 database. In a separate cohort of rats, mitochondria were isolated from skeletal and cardiac muscle and maximal oxidation rates were measured using an Oroboros O2k when provided either pyruvate or fatty acid substrates. Results: The expression of mitochondrial genes are significantly upregulated in HCR skeletal muscle in both male and female rats. In respirometry experiments, fatty acid oxidative capacities were greater in HCR compared to LCR, and male compared to female rats, as a function of both mitochondrial quality and mitochondrial density. This effect was greater in the skeletal muscle than in the heart. Pyruvate oxidation did not differ significantly between lines. Conclusions: The capacity for increased fatty acid oxidation in the HCR rat is a result of selection for running capacity and is likely a key contributor to the healthy metabolic phenotype of individuals with high CRF.